A Semantic Analysis of Pro-Palestine and Pro-Israel Hashtags on Selected News and Media Instagram Accounts - Ismail, Ahmad; Hafidz, Naufal (JLA (Jurnal Lingua Applicata), 2024)
The study aims to investigate the hashtags used by selected news and media Instagram accounts associated with pro-Palestine and pro-Israel viewpoints amid the ongoing 2023 conflict. The study employed a qualitative descriptive approach due to the written format of the data. The study utilized the Flourish website's analysis software to identify prevalent hashtags within a specific timeframe from 1st to 7th November 2023.  The hashtags data taken were in a limited period between 1st and 7th November 2023. Through a semantic approach, these hashtags were examined to reveal their nuanced meanings and representations, particularly in relation to support for each side. The present study analyzing 1825 hashtags from 5 pro-Palestine accounts and 1255 hashtags from 5 pro-Israel accounts revealed distinct hashtag preferences for each group. In the first stage of analysis, after excluding neutral hashtags, #Gazaunderattack emerged as the most prominent hashtag among pro-Palestine accounts, while pro-Israel accounts predominantly used #HamasisIsis. In the second stage, without excluding any hashtags, #Palestine was the dominant tag for pro-Palestine accounts, while pro-Israel accounts prominently used the #Israel hashtag. These hashtags carry distinct connotations depending on their context of usage. By employing a semantic analysis of Instagram hashtags, this study sheds light on the significant role of social media within the linguistic landscape, particularly in expressing and shaping support for conflicting perspectives.